Ligand-activated RXFP1 gene therapy ameliorates pressure overload-induced cardiac dysfunction - Sasipong, Nuttarak; Schlegel, Philipp; Wingert, Julia; Lederer, Christoph; Meinhardt, Eric; Ziefer, Amelie; Schmidt, Constanze; Rapti, Kleopatra; Thöni, Cornelia; Frey, Norbert; Most, Patrick; Katus, Hugo; et al. (Molecular therapy, 2021)
Recurrent episodes of decompensated heart failure (HF) represent an emerging cause of hospitalizations in developed countries with an urgent need for effective therapies. Recently, the pregnancy-related hormone relaxin (RLN) was found to mediate cardio-protective effects and act as a positive inotrope in the cardiovascular system. RLN binds to the RLN family peptide receptor 1 (RXFP1), which is predominantly expressed in atrial cardiomyocytes. We therefore hypothesized that ventricular RXFP1 expression might exert potential therapeutic effects in an in vivo model of cardiac dysfunction. Thus, mice were exposed to pressure overload by transverse aortic constriction and treated with AAV9 to ectopically express RXFP1. To activate RXFP1 signaling, RLN was supplemented subcutaneously. Ventricular RXFP1 expression was well tolerated. Additional RLN administration not only abrogated HF progression but restored left ventricular systolic function. In accordance, upregulation of fetal genes and pathological remodeling markers were significantly reduced. In vitro, RLN stimulation of RXFP1-expressing cardiomyocytes induced downstream signaling, resulting in protein kinase A (PKA)-specific phosphorylation of phospholamban (PLB), which was distinguishable from β-adrenergic activation. PLB phosphorylation corresponded to increased calcium amplitude and contractility. In conclusion, our results demonstrate that ligand-activated cardiac RXFP1 gene therapy represents a therapeutic approach to attenuate HF with the potential to adjust therapy by exogenous RLN supplementation.
Gesehen am 11.10.2021